Lymphangioleiomyomatosis of the lungs: features of the clinical picture, diagnosis and treatment. Case report - Galina L. Ignatova; Elena V. Blinova; Mariia S. Bel'sner (ZAO "Consilium Medicum", 2022)
The article highlights the main issues of etiology, pathogenesis, clinical picture, diagnosis and treatment of patients with lymphangioleiomyomatosis. The clinical observation presents the features of the condition, the rate of progression, diagnostic approaches and management programs for a patient with a rare cystic lung pathology.